EFFECT OF HEAT TREATMENT ON ANTIMICROBIAL ACTIVITY OF CRUDE EXTRACTS OF SOME ARMENIAN HERBS (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
The goal of this research was to explore the thermostability of active antimicrobial constituents of some Armenian herbs. The following herbs were used: Agrimonia eupatoria, Hypericum alpestre, Rumex obtusifolius and Sanguisorba officinalis. Thermal stability was determined by exploring plant extracts antimicrobial activity against Staphylococcus aureus MDC 5233 before and after heat treatment. Antimicrobial activity of the plant extracts was tested by agar well diffusion assay. Broth microdilution assay was used for determination of minimal inhibitory concentrations of the plant extracts. According to obtained data, some of the plant crude extracts retained their antimicrobial activity even after 121ºC heat exposure. In contrast, other plant extracts have lost their activity after treating just with 60ºC. Thus, obtained results about thermostability of compounds responsible for plant extracts antimicrobial activity will allow to choose appropriate temperature ranges during processing of the tested plant materials in order to maintain their antimicrobial activity.
Keywords: plant material, thermal stability, plant crude extract, antimicrobial activity, minimum bactericidal concentration